Foresight study on dairy farming systems in Central Kenya and north of Senegal - Perin, Lucie; Enahoro, Dolapo K. (Frontiers Media, 2023)
Dairy farming activities play important roles in nutrition and health, livelihoods and employment, and culture, in Kenya and Senegal. Faced with various challenges such as climate change, increased populations, insecurity, and conflicts over (water, land, feed) resources, dairy production systems will have to undergo changes in the future that allow them to adapt. This study used a qualitative foresight approach that is mainly based on interviews with technical experts and key stakeholders, including dairy cattle herders, to identify the main evolution trends to be observed in dairy farming in Central Kenya and north of Senegal. It found that (semi)-intensification of production systems and increased settlement of herders who are nomad pastoralists are the prevailing trends. These trends are likely to persist into the future. For both countries, the key drivers of change and their potential environmental and socio-economic impacts were investigated. As dairy systems continue to confront challenges related to livestock feed and water availability, milk quality and safety, production costs, and market access, strategies are needed that can improve resilience of the systems while attaining the right balance between productivity and sustainability.